2010
DOI: 10.1002/aic.12430
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow with injection through a long dead‐end cylindrical porous tube: Application to a hollow fiber membrane

Abstract: Effects of membrane length and hydraulic resistance on the steady-state laminar flow of a fluid with injection in a dead-end cylindrical porous tube have been investigated using the perturbation approach of the Navier-Stokes and continuity equations. Analytic solutions of the dynamic equations, reduced to non linear differential equations, were obtained and applied to submerged, dead-end hollow fiber membranes of large resistances and small wall Reynolds numbers. The velocity and pressure profiles were solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…In order to incorporate the effect of variation in viscosity (either due to concentration polarization or due to temperature gradient) in a weakly permeable or impermeable tube, one can use the concept of effective viscosity being introduced in the present work through equation (12). For the case where integration of viscosity term is diffi cult, numerical integration using equation (13) can be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to incorporate the effect of variation in viscosity (either due to concentration polarization or due to temperature gradient) in a weakly permeable or impermeable tube, one can use the concept of effective viscosity being introduced in the present work through equation (12). For the case where integration of viscosity term is diffi cult, numerical integration using equation (13) can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…(10) as follows: Substituting Eq. (7) and rearranging we get (12) In a practical situation, however, the viscosity of a fl uid depends on the local conditions of temperature and composition; therefore, a suitable function representing the variation of viscosity in terms of r that can be used for integrating Eq. (12) may not be known.…”
Section: Modeling Flow Through Tubular Hollow--fibersmentioning
confidence: 99%
“…Revised manuscript AIChE-15-16842R2 for submission to AIChE Journal 16 repeated three times to confirm the reproducibility of the experimental data.…”
Section: Local Flux Measurementsmentioning
confidence: 99%
“…Especially, Kim et al 16 described a perturbation approach of the Navier-Stokes and continuity equations to investigate the effect of membrane length and hydraulic resistance on the steady-state laminar flow of the fluid in the fiber lumen. It indicated that the flow velocity in fiber lumen represents the exponential variation along the axial direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation